Recovery of Iron Values from Sub Grade Iron Ore through Modeling and Optimisation of Multigravity Separation: A Study Using Three Level Three Factor Box Behnken Design - Gottumukkala Venkateswara Rao; Ravvala Markandeya; Rajan Kumar (Current Approaches in Engineering Research and Technology Vol. 5, 2024)
With the gradual depletion of the high-grade iron ore reserves, it becomes obligatory on the part of the mining industry to consider the exploitation and utilization of low/lean grade ores. In the present investigation, the emphasis was on the development of a cost-effective process flow sheet to benefit these ores to make them suitable for the user industry. In this study, a three-level, three-factor Box- Behnken factorial design combined with Response Surface Methodology (RSM) for modeling of process parameters of Multi Gravity Separator (MGS) for recovery Iron values from sub-grade iron ore, Deposit No. 5, Bailadila complex has been developed. The three significant operational parameters of MGS, Drum rotational speed, Drum inclination and wash water Flow rate were considered in the experimental work and all other parameters like feed percent solids, shake frequency and shake amplitude were maintained constant. The ’as received’ sub-grade iron ore sample is an admixture of lump and fines and chemically assayed and Loss on Ignition (LOI). Experiments were conducted with representative sample ground to -100 mesh as per the design matrix. The obtained results were evaluated with the Box-Behnken factorial design, RSM and also Quadratic programming (QP). Second-order response functions were developed for a grade ( and recovery (% yield) of the concentrate fraction. Taking advantage of quadratic programming (QP), it was observed that a maximum grade of achieved at a drum inclination of 3 degrees, wash water flow rate of 6 Liters Per Minute (LPM) and a drum rotational speed of 175 Revolutions Per Minute (RPM). Similarly, a maximum concentrate recovery (Yield) of by weight could be achieved at 5 degrees drum inclination, 2 LPM wash water flow rate and a drum rotational speed of 225 RPM. Predicted values of responses obtained using model equations were in good agreement with the experimental values. The influence of the process variables of multi gravity separator on concentrate grade and recovery was discussed. This finding proved that Box–Behnken design, response surface methodology could efficiently be applied for modeling of some sub-grade iron ore from Bailadila and that it is an economical way of obtaining the maximum amount of information in a short period of time and with the fewest number of experiments.